The losses by difficulty of communication in health care for the deaf person: integrative review (Research, Society and Development, 2022)
Generally, the services in general, including health care, are not properly prepared for the reception of people with deaf blindness, the nursing professionals, in large part, demonstrate unpreparedness in understanding the population with special needs, interfering directly in the quality of care offered, in this context, the need to discuss issues that cover the accessibility of this audience to health services stands out. Given this, this work has as its primary objective to know the damage by the difficulty of communication in the care of nursing professionals to the deaf person, and as secondary objectives: to understand what are the causes of this difficulty in providing health care to the deaf and sensitize nurses about the importance of sign language in the area of health. The research was an integrative review, which is a method that includes analysis of relevant research that enhances decision making and improvement of clinical practice. It is the construction of an extensive evaluation of the literature, contributing to discussions about methods and results of research on the damage by the difficulty of communication in health care to deaf people, as well as conducting future studies. It was noticeable with the findings about the study, about the benefits of a specialized and appropriate care for the deaf patient by the nursing professional, in addition to losses allied to this need if not met, such as dissatisfaction, fear, decreased search, misdiagnoses.